Serupa tapi Tak Sama: Menelisik Strategi Adaptasi Expatriat Indonesia pada Pola Komunikasi dalam Budaya Kerja di Negeri Serumpun Malaysia - Marshalya Amanda Putri; Frederic Sebastian Simarmata; Zalfaa Nabila Putri Nafiah; Najwa Farrah Nuryadin; Setiyo Adji Rizqi Shafwan (INDO PUBLISHING, 2026)
countries with roots in the same culture, Indonesia and Malaysia share cultural, linguistic, and ethnic similarities that often lead to the perception of ease in cross-cultural communication. However, the “similar but not the same” phenomenon actually becomes an obstacle for Indonesian expatriates when adapting to the communication patterns of work culture in Malaysia. This study aims to examine in depth the communication challenges and adaptation strategies of Indonesian expatriates in dealing with communication patterns of work culture in Malaysia. Using a qualitative approach with a single case study design, this study involved an Indonesian expatriate who had worked in the Food and Beverage (FnB) sector in Malaysia for four years. Data were collected through in-depth interviews and analyzed using thematic analysis referring to the steps of Braun & Clarke (2006). The results showed that the main obstacles were multidimensional, including differences in disciplinary systems and work structures, disorientation towards hierarchical relations that were actually more egalitarian than expected, and differences in norms in providing feedback and work formalities. Meanwhile, adaptation strategies developed by expatriates included observation and social learning. This study confirms that cultural similarities and similarities do not guarantee smooth cross-cultural communication; In fact, invisible differences are the primary arena for adaptation. These findings add to our understanding of expatriate adaptation within a similar cultural context and provide practical benefits for cross-cultural preparation prior to assignments in Malaysia.